Pengaruh Pemberian Ekstrak Daun Pepaya Untuk Mengendalikan Ulat Grayak Pada Tanaman Edamame (Glycine max (L) Merril) - Mangan, Diky Hernika; Rizali, Akhmad; Sofyan, Antar (Universitas Lambung Mangkurat, 2023)
One of the obstacles that inhibit edamame plants is the armyworm (Spodoptera litura) because it can cause crop failure and large losses. The purpose of this study was to determine the effect of various concentrations of papaya leaf extract to control armyworm attacks on edamame plants. The design in this study used a Completely Randomized Design (CRD) with one factor treatment P1 (Control), P2 (10% Concentration), P3 (20% Concentration), and P4 (30% Concentration). Each treatment was repeated 5 times, so that 20 experimental units were obtained. This research was carried out at the Production and Greenhouse Laboratory of the Department of Agroecotechnology, Faculty of Agriculture, Lambung Mangkurat University, as well as at the Chemical and Industrial Environment Laboratory, Department of Agricultural Industrial Technology, Faculty of Agriculture, Lambung Mangkurat University. This study was conducted from February to March 2021. The results of this study showed that P4 (30% Concentration) showed the highest average mortality with 80% mortality and was significantly different from other treatments. Treatment P4 (30% Concentration) also showed the highest average pest mortality rate with 1.2 heads/hour. The LC50 value of papaya leaf extract against armyworm (Spodoptera litura) was 9616 ppm at 72 hours after application. The higher the concentration of papaya leaf extract applied, the faster it can control the armyworm (Spodoptera litura).